Adjacent Construction Impact of Shield Tunnel Undercrossing High-Speed Railway Tunnels Based on Surrounding Rock Creep Effect - WANG Youqi; MA Guosong; QIU Wenge; HUANG Haiyun; ZHANG Du; AI Xufeng (Chengshi guidao jiaotong yanjiu)
[Objective] When the surrounding rock exhibits creep characteristics, the temporal factors in the adjacent construction process of shield tunnel undercrossing high-speed railway tunnels cannot be ignored. The speed of the adjacent construction may affect the time-dependent deformation behavior of the surrounding rock, thereby influencing the track settlement in the high-speed railway tunnels. Therefore, it is necessary to study the impact of adjacent construction of shield tunnel undercrossing the high-speed railway tunnels under the creep effect of the surrounding rock. [Method] In the case study of Changsha Metro Line 3 shield tunnel undercrossing the Liuyanghe Tunnel, based on the Cvisc creep model, the FLAC 3D finite difference software is used for numerical simulation. The impacts of the adjacent construction on surrounding rock under the classical elastoplasticity and the creep effect are compared and analyzed, together with the time-related factor influence like the driving speed of shield tunneling on the adjacent construction. [Result & Conclusion] Increased water content of argillaceous siltstone will lead to an increase in the final settlement deformation of high-speed railway tracks. So, the water content of the surrounding rock must be prioritized in creep effect analysis. Considering the creep effect of the surrounding rock and the time lag characteristics exhibited in the high-speed railway track settlement deformation during excavation, the creep effect of the surrounding rock may contribute positively to the deformation control in the above adjacent construction scenario. With the acceleration of the shield tunneling, the time lag becomes more obvious in the settlement deformation of the high-speed railway track. During adjacent construction, the creep effect of the surrounding rock can be fully utilized through "rapid excavation and prompt support" to achieve the goal of "trading time for space," thereby securing additional safety margins for the track post-construction settlement control.